PENERAPAN UNSUR TINDAK PIDANA KORUPSI PADA PELAKSANAAN PROGRAM KEMITRAAN DAN BINA LINGKUNGAN (Studi Putusan Perkara Nomor 6/Pid.Sus-TPK/2016/Pn.Pdg dan Nomor 07/Pid.Sus-TPK/2016/PN.Pdg) - zulkifli, Zulkifli; Fitriati, Fitriati; ferdi, ferdi (LPPM Universitas Ekasakti Padang, 2018)
In the law enforcement of corruption, there are at least 2 (two) articles that are often used to ensnare the defendant, namely Article 2 paragraph (1) and Article 3 of Law Number 20 Year 2001 regarding the Amendment of Law Number 31 Year 1999 regarding Eradication of Corruption. In practice, the provision has been applied by the Judge in the decision of corruption case in the implementation of partnership program and environment development with the actors from the private sector, as the Manager of Lubuk Alung Regional IV branch PT. Sang Hyang Seri (Persero) is found guilty because it has been proven legally and convincingly committed a criminal act of corruption by misusing and using the. Community Development Program fund from PT. Angkasa Pura and PKBL funds from PT. Pertamina and PT. Bukit Asam